Evolutionary and organismic constraints on the relationship between spacer length and environmental conditions in clonal plants - Klimešová, J. (Jitka); Doležal, J. (Jiří); Sammul, M. (Oikos, 2011)
The rate of lateral spread of clonal plants is considered a plastic trait that responds directly to environmental conditions. However, this response is likely constrained by evolutionary history and other species attributes. Here we ask how the relationships between lateral spread and the distribution of herbaceous plant species in different environments are influenced by the type of spacer (epigeogenous versus hypogeogenous rhizome), its persistence (integrator versus splitter), and the height and phylogeny of the plant. Analysis of spacer length of 367 species from temperate to arctic Europe revealed that other plant characteristics modulate the relationship between spacer length and environmental conditions.